Exploring environmental and distributional impacts of different transition pathways for healthier and sustainable diets: An economic modelling study - Kuiper, Marijke; de Lange, Thijs; van Zeist, Willem-Jan; van Meijl, Hans (Elsevier, 2025)
Background The EAT–Lancet (EL) report made a convincing case that a transformative diet shift could yield substantial health benefits while helping to respect key planetary boundaries. Shifting to a more plant-based EL diet requires an unprecedented break from historic trends of rising meat consumption. By exogenously shifting diets, existing studies do not provide guidance on how to shift diets. In this study, we model specific policies that might achieve such a dietary shift and their potential economic, environmental, and distributional impacts.